PENGARUH KOMUNIKASI, KONFLIK, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN (Studi Kasus di Perusahaan Perak Tom’s Silver Yogyakarta) - Wibowo, Fx. Pudjo (Universitas Slamet Riyadi, 2018)
The purpose of this paper is to determine the extent of the influence of communication, conflict, work stress and work environment to employee work productivity at Silver Company Tom 'Silver Yogyakarta. From the results of analysis shows that there is influence simultaneously (together) between communication, conflict, work stress and work environment of work, to work productivity of employees. This results also shows thatcommunication (X1) and working environment have a significant effect on employee work productivity (Y). The variables of conflict (X2) and work stress (X4) are shows the different results. Both of them show that there are haven’t significant effect to employee work productivity (Y).R Square (R2) shows that the magnitude of the effect of communication, work conflict, work stress and work environment on employee work productivity is 52.2% and 47.8 % influenced by other factors. Keywords: Communication, Conflict, Work Stress, Work Environment, Work Productivity.